Human factor implementation in the automotive sector as a model of cooperation between university and company - Atuesta Reyes, Juan David; Universidad Católica de Pereira (Universidad Católica de Pereira, 2018)
In this article the results of a study carried out with 155 university students are collected, during different academic periods, in which their performance was analyzed when facing the professional demand which involves the use of a problem-based learning methodology (PBL). Within the framework that promotes the implementation of alternatives to traditional teaching methods, the project that has linked university and company has been studied, through specific cooperation between the Industrial Design program of Universidad Católica de Pereira and the local industry, specifically the company Busscar de Colombia. Through the systematic development of joint activities, developed in different school periods, it can be concluded that the application of the methodology PBL has achieved a high success rate, since at the end of the process, the students had presented ninety-two (92) design proposals adjusted to the needs and interests of use of the prototypical users.